miR-24-3p/KLF8 Signaling Axis Contributes to LUAD Metastasis by Regulating EMT - Pengyu Jing; Nianlin Xie; Nan Zhao; Ximing Zhu; Pei Li; Guizhou Gao; Haizhou Dang; Zhongping Gu (Journal of Immunology Research)
Reprogramming of the tumor immune microenvironment is a salient feature during metastasis in LUAD. miR-24-3p and KLF8, which are key regulators of the tumor immune microenvironment, had been proved to show metastasis-promoting property in LUAD. However, whether miR-24-3p could regulate LUAD metastasis by targeting KLF8 remains unclear. This study explored the functions and mechanisms of miR-24-3p/KLF8 signaling in advanced LUAD. The expression level of miR-24-3p and KLF8 were tested in LUAD patients, and the corelation of miR-24-3p and KLF8 was evaluated. The interaction of miR-24-3p and KLF8 was demonstrated by luciferase reporter activity assay, in vitro migration and invasion studies, and in vivo metastatic studies. miR-24-3p level was downregulated in LUAD and negatively associated with KLF8 mRNA expression. miR-24-3p controls LUAD metastasis by directly targeting KLF8 and inducing Snail and E-cadherin expressions. Targeting the miR-24-3p/KLF8/EMT axis might be of great therapeutic value to advanced LUAD patients.